Fisioterapia con ondas de choque en pacientes adultos con epicondilitis. Hospital Básico 11 BCB Galápagos, 2019 - Gilda Magaly, Gutierrez Pilco (2019)
The extracorporeal shockwave (OCE) represent early treatment of musculoskeletal disorders due to their physical mechanism Mechanotransduction providing analgesia which is its physiological and foundation basics, this effect comes with vasodilatation that occurs on the activation zone which allows angiogenesis factors influence growth and recruitment of stem cells, consecuently it tends to tissue regeneration of tendon and muscle injuries. The research project aims to include in the protocol of physiotherapy treatment of epicondylitis using extracorporeal shock waves to determine the level of functionality recovered from patients attended the 11 BCB Galapagos Basic Hospital. A field study in which 35 patients with an epicondylitis diagnosed where included, also a physiotherapeutic medical history was applied with start and end evaluations of the performed treatment, it also includes a numerical pain scale, goniometer test, Daniels test and diagnostic tests, according to the data obtained by the numerical pain scale where a higher incidence by the degree of severe pain is evidenced. The statistical data held in relation to the degree of pain, range of motion and muscle strength is verified at the end of treatment, the pain reduced and increased both muscle strength and range of motion, confirming that the implementation of the OCE in the conventional physical therapy gives positive results in the recovery of the patient with epicondylitis.